Análise da ocorrência de Hipotermia no paciente cirúrgico: da entrada à saída da sala de operação - Maria Inês Santos Rossi (2021)
Introduction: Hypothermia is a common event in the perioperative period and causes complications related to the patient such as tremors, changes in metabolism and the coagulation system, cardiovascular events, increased risk for the development of diseases. The operating room is a favorable environment for the development of hypothermia, due to the inhibition of thermoregulation mechanisms caused by anesthesia and exposure to low ambient temperatures. Objective: To analyze the patient's body temperature when entering and leaving the operating room. Method: This is an observational study that analyzed data from 123 patients who underwent anesthetic-surgical procedures at a large university hospital in Minas Gerais, in November and December 2020. Measurement of tympanic body temperature and environment occurrences when entering and leaving the operating room. To verify the influence of the variables, univariate analysis was performed using hypothesis tests using the Forward method, which selected -variables with p-value <0.25. Then, multivariate logistic regression was performed using the Backward method, considering a 5% significance level for variable selection. Results: There was a predominance of females, aged over 60 years, physical classification by the American Society of Anesthesiologists of II and III, classification of normal weight according to the Body Mass Index, conventional surgery and general anesthesia. The mean body temperature at the entrance and exit of the operating room was 36.58ºC and 35.56ºC, respectively, (difference of -1.02ºC), 90 (73.2%) patients had hypothermia. In the final model of the multivariate analysis, there was a significant influence on the classification of body temperature when leaving the operating room of the following variables: Body Mass Index (p-value 0.006), American Society of Anesthesiologists classification (p- value 0.032), type of surgery (p-value 0.008), body temperature at the entrance to the operating room (p-value 0.004) and operating room temperature difference (p-value 0.040). The implementation of passive 90 (73.2%) and 33 (26.9%) active prevention methods was observed, but they did not exert a significant influence on the occurrence 10 of hypothermia. No significant influence of hypothermia on peripheral oxygen saturation and blood pressure was identified. Conclusion: the results showed that the frequency of intraoperative hypothermia is high, influenced by avoidable factors such as body temperature at the entrance to the operating room and temperature difference in the operating room, as well as the type of surgery, Body Mass Index and classification of the American Society of Anesthesiologists. It is essential that nurses implement actions to prevent hypothermia, to avoid complications and discomfort caused by it, and to promote improvement in the care provided to surgical patients.